Practical Aspects of Software Optimization for MCUs with RTOS - Шевцов, І. О.; Свид, І. В.; Чумак, В. С.; Сєріков, А. О. (MC&FPGA, 2022)
This paper is focused on some practical aspects of optimization of MCU software written in C programming language using RTOS. Machine-specific optimizations and RTOS specific optimizations are described.
Keywords: optimization; RTOS; MCU; periphery